2016
DOI: 10.1007/s10926-015-9624-z
|View full text |Cite
|
Sign up to set email alerts
|

Process Evaluation of a Workplace Integrated Care Intervention for Workers with Rheumatoid Arthritis

Abstract: Purpose To perform a process evaluation of the implementation of a workplace integrated care intervention for workers with rheumatoid arthritis to maintain and improve work productivity. The intervention consisted of integrated care and a participatory workplace intervention with the aim to make adaptations at the workplace. Methods The implementation of the workplace integrated care intervention was evaluated with the framework of Linnan and Steckler. We used the concepts recruitment, reach, dose delivered, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Their explanations for this low protocol adherence were similar to the barriers mentioned by the stakeholders in our study, namely, organizational constraints and limited availability of suitable workplaces (36,37). Furthermore, in a recent study about an integrated workplace intervention for Dutch workers with rheumatoid arthritis, Van Vilsteren et al (38) found that it was difficult to implement an integrated care approach. This is in line with an earlier Dutch study by Anema et al (39) that revealed limited collaboration between OHC professionals and other healthcare providers in the Netherlands.…”
Section: Rtw Program For Workers Without a Contract Sick-listed For supporting
confidence: 65%
“…Their explanations for this low protocol adherence were similar to the barriers mentioned by the stakeholders in our study, namely, organizational constraints and limited availability of suitable workplaces (36,37). Furthermore, in a recent study about an integrated workplace intervention for Dutch workers with rheumatoid arthritis, Van Vilsteren et al (38) found that it was difficult to implement an integrated care approach. This is in line with an earlier Dutch study by Anema et al (39) that revealed limited collaboration between OHC professionals and other healthcare providers in the Netherlands.…”
Section: Rtw Program For Workers Without a Contract Sick-listed For supporting
confidence: 65%
“…The reach of the current study was not as high as for example the study performed by Buist et al, where the reach was 22.4% in an integrated healthcare system [ 18 ]. It must be noted that assessing the actual reach of a target population in implementation research is hard to measure, as is also discussed by Van Vilsteren et al in their process evaluation of a workplace intervention for workers with rheumatoid arthritis [ 19 ]. For example, the amount of patients that were invited to participate could have been an overestimation, since the HCPs inviting the patients could have excluded patients without reporting exclusions to the research team.…”
Section: Discussionmentioning
confidence: 99%
“…The audio-recording of each therapist's initial treatment session with one participant (up to n=40) will be listened to by members of the research team, using a structured delity checklist, to assess whether the therapist went through the assessment process appropriately, identi ed and appropriately prioritized the participant's problems, planned, and commenced an appropriate treatment plan. The completed WES-RC and the accompanying trial treatment notes for that participant will also be analyzed to evaluate whether the problems, plan and solutions, as discussed, were recorded in the WES-RC and the treatment notes record the ful llment of the treatment plan [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…We have therefore prioritised what is achievable within limited resources. To our knowledge, one other JRVR trial in arthritis has conducted a process evaluation [31]. This focused on implementation (recruitment, reach, dose, treatment delity and satisfaction).…”
Section: Discussionmentioning
confidence: 99%